2016
DOI: 10.1051/0004-6361/201526872
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic signatures of AGN feedback in moderately powerful radio galaxies atz~ 2 observed with SINFONI

Abstract: Most successful galaxy formation scenarios now postulate that the intense star formation in massive, high-redshift galaxies during their major growth period was truncated when powerful AGNs launched galaxy-wide outflows of gas that removed large parts of the interstellar medium. SINFONI imaging spectroscopy of the most powerful radio galaxies at z ∼ 2 show clear signatures of such winds, but are too rare to be good representatives of a generic phase in the evolution of all massive galaxies at high redshift. He… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 100 publications
2
17
0
Order By: Relevance
“…These values are roughly consistent with similar spectroscopic studies of [OIII] emission (e.g. Vega Beltrán et al 2001;Mullaney et al 2013;Collet et al 2016;Harrison et al 2016;Sun et al 2017). We note that most of these works cite the w 80 measurement for their objects, the velocity difference between the 10th and 90th percentiles of the emission line, roughly the FWHM of a single Gaussian fit.…”
Section: Individual Targetssupporting
confidence: 89%
See 1 more Smart Citation
“…These values are roughly consistent with similar spectroscopic studies of [OIII] emission (e.g. Vega Beltrán et al 2001;Mullaney et al 2013;Collet et al 2016;Harrison et al 2016;Sun et al 2017). We note that most of these works cite the w 80 measurement for their objects, the velocity difference between the 10th and 90th percentiles of the emission line, roughly the FWHM of a single Gaussian fit.…”
Section: Individual Targetssupporting
confidence: 89%
“…We note that most of these works cite the w 80 measurement for their objects, the velocity difference between the 10th and 90th percentiles of the emission line, roughly the FWHM of a single Gaussian fit. Our broad component FWHM therefore overestimate these measurements but likely still satisfy the w 80 > 600 km s −1 criterion outlined in Collet et al (2016) and Liu et al (2013) indicative of either ionised outflows or highly turbulent material. These objects are potentially of interest for further study with highly resolved imaging to understand their host properties and the location of the turbulent or outflowing material.…”
Section: Individual Targetsmentioning
confidence: 47%
“…The first step could be an assessment of how many sources with radiatively driven winds also have radio emission, as recent evidence seems to point out to a frequent coexistence of both (see e.g. Nesvadba et al 2008;Collet et al 2016;Harrison et al 2015), but we still need to assess whether in the most luminous sources the radio emission is actually produced by jets and lobes or just by particles accelerated in wind-driven shocks (e.g. Nims et al 2015;Zakamska et al 2016), and what fraction of the observed outflows is actually produced by star formation, rather than the AGN (Sarzi et al 2016).…”
Section: Jet Vs Radiative Outputmentioning
confidence: 99%
“…Binney & Tabor 1995;Soker et al 2001;Gaspari et al 2012). However, relativistic jets are also expected to be one of the major drivers of feedback on galactic scale, as supported by several observational evidences of jet-ISM interaction (a few recent works being Mahony et al 2016;Collet et al 2016;Dasyra et al 2015;Morganti et al 2015;Ogle et al 2014;Dasyra et al 2014;Morganti et al 2013;Lanz et al 2015b;Tadhunter et al 2014;Nesvadba et al 2011Nesvadba et al , 2008Nesvadba et al , 2007. However, only a few theoretical papers (Sutherland & Bicknell 2007;Gaibler et al 2011;Wagner & Bicknell 2011b;Gaibler et al 2012;Wagner et al 2012) have addressed the question of how a relativistic jet interacts with a multi-phase ISM of the host galaxy, and over what scales such interactions are relevant.…”
Section: Introductionmentioning
confidence: 99%